2015
DOI: 10.1371/journal.pone.0131733
|View full text |Cite
|
Sign up to set email alerts
|

Interference and Mechanism of Dill Seed Essential Oil and Contribution of Carvone and Limonene in Preventing Sclerotinia Rot of Rapeseed

Abstract: This study aimed to evaluate the inhibitory effects of dill (Anethum graveolens L.) seed essential oil against Sclerotinia sclerotiorum and its mechanism of action. The antifungal activities of the two main constituents, namely carvone and limonene, were also measured. Mycelial growth and sclerotial germination were thoroughly inhibited by dill seed essential oil at the 1.00 μL/mL under contact condition and 0.125μL/mL air under vapor condition. Carvone also contributed more than limonene in inhibiting the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 41 publications
(42 reference statements)
3
44
0
Order By: Relevance
“…Methyl salicylate is only weakly antifungal against A. niger, C. albicans, or C. neoformans, but eugenol is somewhat active (see Table 13). Monoterpene hydrocarbons such as α-pinene, β-pinene, limonene, or myrcene show only weak antifungal activity (Table 13) and are not expected to contribute to the antifungal activities of the essential oils unless there are synergistic effects of these components (see, for example [101,102]). The mechanisms of antifungal activity of essential oils are poorly understood.…”
Section: Smallanthus Uvedalia (L) Mackmentioning
confidence: 99%
“…Methyl salicylate is only weakly antifungal against A. niger, C. albicans, or C. neoformans, but eugenol is somewhat active (see Table 13). Monoterpene hydrocarbons such as α-pinene, β-pinene, limonene, or myrcene show only weak antifungal activity (Table 13) and are not expected to contribute to the antifungal activities of the essential oils unless there are synergistic effects of these components (see, for example [101,102]). The mechanisms of antifungal activity of essential oils are poorly understood.…”
Section: Smallanthus Uvedalia (L) Mackmentioning
confidence: 99%
“…Another important factor that has been detected is the synergistic action of A. graveolens essential oil components, as observed by Ma et al (2015) who, upon evaluating the activity of this oil against the fungus Sclerotinia sclerotiorum, found that two of its main components, carvone and limonene, synergistically inhibited the growth of this fungus. Limonene is found in oils from different plants with anthelmintic activity, such as Lippia sidoides, Cymbopogon martinii, Mentha piperita and Eucalyptus staigeriana (Katiki et al, 2011;Carvalho et al, 2012;Ribeiro et al, 2013).…”
Section: Discussionmentioning
confidence: 92%
“…Macedo et al (2009), using Eucalipypus globulus essential oil, obtained 99.3% HI at the 21.75 mg/mL, and Pessoa et al (2002), upon evaluating Ocimum gratissimum, found a 100% HI at 50 mg/mL concentration. Although some plants may present common components, these differ in concentration levels; also, the anthelmintic action can be potentiated by a synergistic effect between different components (Katiki et al, 2017;Ma et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Caraway essential oil had the antimicrobial effects due to its content of basic constituents of monoterpenes, carvone and limonene. The basic constituents had a permeability effect on fungal cell membrane, inactivation of some organic compounds and enzymes and/or the inhibition of conidial germination, eventually, the death of fungal pathogen [13]. Moreover, the use of essential oils in storage of JA may have many benefits, including, they are natural-ecofriendly products, biodegradable and multifunctional purposes.…”
Section: Severity Of Diseasementioning
confidence: 99%